Stable Sodium Metal Batteries via Manipulation of Electrolyte Solvation Structure. Issue 5 (25th February 2020) - Wang, Shiyang; Chen, Yawei; Jie, Yulin; Lang, Shuangyan; Song, Junhua; Lei, Zhanwu; Wang, Shuai; Ren, Xiaodi; Wang, Dong; Li, Xiaolin; Cao, Ruiguo; Zhang, Genqiang; et al.
Abstract: Sodium metal batteries have attracted rapidly rising attention due to their low cost and high energy densities. However, the instability and low efficiency of metallic sodium anodes pose significant concerns for their practical applications. Here a highly stable sodium metal anode enabled by an ether‐based electrolyte is reported, which exhibits a long‐term stable cycling up to 400 cycles and achieves an unprecedentedly average Coulombic efficiency of over ≈99.93%. It is revealed that the organic/inorganic hybrid structure containing B–O species and NaF in the ultrathin solid‐electrolyte interphase layer plays the key role for the outstanding electrochemical performances. Furthermore, a Na||Na3 V2 (PO4 )3 full cell successfully achieves a stable cycling performance that paves the way for the development of sodium metal batteries. Abstract : Sodium metal batteries are potential electrochemical energy storage devices with high energy density and low cost. A stable sodium metal anode is realized by manipulating electrolyte solvation structure, showing a high Coulombic efficiency up to 99.93% and ultralong lifespan over 400 cycles. This work provides a strategy for developing practical sodium metal batteries.